Demand for 'Safe Spaces' : Avoiding Harassment and Stigma - Kondylis, Florence (World Bank, Washington, DC, 2020)
What are the costs to women of harassment on public transit? This study randomizes the price of a women-reserved “safe space” in Rio de Janeiro and crowd-source information on 22,000 rides. Women in the public space experience harassment once a week. A fifth of riders are willing to forgo 20 percent of the fare to ride in the “safe space”. Randomly assigning riders to the “safe space” reduces physical harassment by 50 percent, implying a cost of $1.45 per incident. Implicit Association Tests show that women face a stigma for riding in the public space that may outweigh the benefits of the safe space.